REPRESENTATION OF NETIZENS' EMOTIONS THROUGH EXPRESSIVE SPEECH IN YOUTUBE COMMENTS: A PRAGMATIC STUDY OF ISA BAJAJ'S VIDEO ON DEDDY CORBUZIER'S CHANNEL - syadinov surya pratama; Asnawi (SOSIOEDUKASI, 2025)
The development of social media has changed people's communication patterns to be more participatory, dialogical, and full of emotional expressions. YouTube, as one of the digital public spaces, provides a comment column that allows netizens to openly express their attitudes, feelings, and judgments towards the content consumed. This study aims to describe and analyze the form and function of expressive speech used by netizens in the comment column of the YouTube video "Isa Bajaj" on Deddy Corbuzier's channel. This study uses a descriptive qualitative approach with data in the form of 500 purposively selected netizens' comments. Data analysis was carried out by referring to John R. Searle's speech theory of actions, especially the category of expressive speech actions. The results showed that there were seven types of expressive speech, namely positive praise/appreciation (29.0%), criticism/disapproval (24.0%), expressions of gratitude/gratitude (16.0%), expressions of anger or negative emotions (14.0%), empathy/compassion (8.0%), regret/apology (5.0%), and hope/prayer (4.0%). The dominance of praise and criticism shows the high emotional and evaluative involvement of netizens in the content of the personal narrative presented. These findings confirm that YouTube's comment column serves as a space for public emotional expression that represents the collective psychological condition of netizens. This research contributes to enriching the study of digital pragmatics by placing expressive speech as a reflection of emotional dynamics, empathy, and moral reflection in social media communication.